2003
DOI: 10.1227/01.neu.0000073547.86747.f3
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Regional Cerebral Oxygen Saturation Monitoring during Carotid Endarterectomy as a Predictor of Postoperative Hyperperfusion

Abstract: Intraoperative rSO(2) monitoring can reliably identify patients at risk for hyperperfusion after CEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 31 publications
1
58
0
Order By: Relevance
“…18,20 Moreover, intraoperative transcranial regional cerebral oxygen saturation is another essential indicator for post-CEA hyperperfusion syndrome. 21 Ascher et al demonstrated that contralateral CEA within 3 months was associated with post-CEA hyperperfusion syndrome; 22 1 of 6 patients with bilateral CEA had the syndrome in this study.…”
Section: Discussionsupporting
confidence: 54%
“…18,20 Moreover, intraoperative transcranial regional cerebral oxygen saturation is another essential indicator for post-CEA hyperperfusion syndrome. 21 Ascher et al demonstrated that contralateral CEA within 3 months was associated with post-CEA hyperperfusion syndrome; 22 1 of 6 patients with bilateral CEA had the syndrome in this study.…”
Section: Discussionsupporting
confidence: 54%
“…Ogasawara et al [13] compared declamping rSO 2 with preclamping values and found a significant correlation between rSO 2 increases after declamping and the onset of CHS. However, in their study, only 1 patient developed CHS.…”
Section: Discussionmentioning
confidence: 99%
“…Positron emission tomography (PET) can be considered the gold standard for determining oxygen extraction fraction (OEF; the amount of oxygen extracted from the blood) and has been widely used to study brain oxygenation in a variety of conditions. [1][2][3][4][5][6][7] However, in the setting of acute stroke management, PET is not a reasonable option for most centers. Near-infrared spectroscopy (NIRS) is a noninvasive and low-cost technique that can measure oxyhemoglobin (HbO 2 ) and deoxyhemoglobin concentrations (HHb) at bedside.…”
Section: Introductionmentioning
confidence: 99%